Price convergence between new and old EU member countries - Santariusová, Markéta (2012)
The main aim of this dissertation is to investigate whether the price convergence between new and old EU member countries occurred. According to development of price level index it is shown that new member countries converge towards the EU27 and that old member countries more or less hover around their initial levels. Germany is chosen to be a benchmark country and thus the development towards Germany is also examined. The results reveal that new member states converge towards the benchmark country. However, in the case of old member states both convergence and divergence occurs. Furthermore, factors that may have an influence on such a development are investigated. The empirical research shows that GDP, hiring regulations and minimum wage and business regulation were of significance during the examined period, from 2000 to 2009 respectively.